Rumohra aconquijana (Dryopteridaceae): a new species endemic from Southern Yungas in Argentina - Marcelo Daniel Arana; Eva Bulacio; Alberto Carlos Slanis; Alfredo Grau (Rodriguésia, 2023)
Abstract Rumohra aconquijana sp. nov., a restricted endemism of the Montane Jungle district (700-1,500 m asl; Yungas biogeographic province) is reported, described and illustrated. Rumohra aconquijana grows as epiphyte on Ocotea porphyria (Lauraceae) and Sambucus peruviana (Viburnaceae) in humid terraces and slopes of the cloud forest. The new species differs from the widespread R. adiantiformis, especially by the dissection of the laminae, the shape and size of the pinnules. Also, there are differences with all Argentinean and Bolivian and Chilean species of Rumohra in the ornamentation of the perispore, which is folded with few folds, partially fused, narrow and with ridged margins. Here, we present the first species of Rumohra endemic from Argentinean Yungas, as well as a key to identifying the species occurring in Argentina and Bolivia.